Core Java 9 : advanced (LiveLessons (Indianapolis, Ind.), 2017)
"In Core Java: Advanced LiveLessons, Cay S. Horstmann takes that same approach to introducing experienced programmers to Java, with detailed demonstration. This training pairs with the tenth edition of Core Java, Volume II, advanced features, which has been fully updated to cover Java SE 8. In these video LiveLessons, you will learn about advanced Java language features along with the most useful parts of the standard library."--Resource description page